COMPARISON OF TOPICAL 0.1% ADAPALENE GEL VERSUS CRYOTHERAPY TREATMENT IN PATIENTS WITH PLANTAR WARTS - Maria Mahboob,; Ahmed, Najia; Rahman, Atiya; Naz, Kiran; Niaz, Furquana; Farooq, Omer (Journal of Ayub Medical College Abbottabad, 2022)
Background: Plantar wart is a common viral infection of the plantar surface of the foot. Multiple treatment modalities are available but there is no definitive management option. The aim of this study is to compare topical adapalene gel 0.1% with cryotherapy in patients presenting with plantar warts in terms of time taken for complete clearance of the lesions. Methods: The study was conducted at the department of Dermatology, PNS Shifa Hospital, Karachi from 28th April to 28th October 2020. Eighty-four patients with plantar warts who fulfilled the inclusion and exclusion criteria were included in the study. Approval from the institutional ethical review committee was sought and written informed consent was taken from all the patients. Patients were divided into two groups, A (Adapalene 0.1% gel) and B (Cryotherapy) of 42 patients each. Adapalene gel was applied twice daily under occlusion at home and cryotherapy was done at the clinic after every two weeks. Patients were followed weekly from the onset of treatment and days taken for complete clearance of plantar warts were noted. Both the groups were compared for the outcome, i.e., time taken for complete clearance of lesions. Results: The mean time for complete clearance of plantar warts in group A was 35.619±3.154 days and in group B, it was 50.404±3.178 days. Conclusion: Adapalene gel 0.1% used for the treatment of plantar warts helped in complete clearance of lesions faster than cryotherapy.